Algebra

Lesson

We've already learnt how to simplify expressions with grouping symbols. To expand an expression like $3\left(x+2\right)$3(`x`+2) or $5\left(2y-1\right)$5(2`y`−1) we use the distributive law:

The Distributive Law

To expand an expression of the form $A\left(B+C\right)$`A`(`B`+`C`), we use the property:

$A\left(B+C\right)$A(B+C) |
$=$= | $A\times B+A\times C$A×B+A×C |

$=$= | $AB+AC$AB+AC |

So far we have used the distributive law to simplify expressions involving multiplication of constants with variables. Now we will look at how to use the distributive law to simplify expressions involving multiplication of variables. We will need to use the multiplication index law.

**Expand:** $5x\left(6x^6-3y\right)$5`x`(6`x`6−3`y`)?

**Think: **We'll expand the brackets using the distributive law:

To evaluate the multiplications $5x\times6x^6$5`x`×6`x`6 and $5x\times\left(-3y\right)$5`x`×(−3`y`), we will use the power rule:

The Power Rule

To multiply like terms with like bases, (e.g. $x$`x` and $x$`x`) we use the rule:

$x^a\times x^b$xa×xb |
$=$= | $x^{a+b}$xa+b |

For example,

$x\times x^2$x×x2 |
$=$= | $x^{1+2}$x1+2 |

$=$= | $x^3$x3 |

Therefore:

$5x\times6x^6$5x×6x6 |
$=$= | $30x^7$30x7 |

$5x\times\left(-3y\right)$5x×(−3y) |
$=$= | $-15xy$−15xy |

**Do:** $30x^7-15xy$30`x`7−15`x``y`

Expand the following:

$r\left(r+5\right)$`r`(`r`+5)

Expand $6u^7\left(9u^7+9u^6\right)$6`u`7(9`u`7+9`u`6)

Expand:

$7wy\left(y+w\right)$7`w``y`(`y`+`w`)

Form and solve linear equations and inequations, quadratic and simple exponential equations, and simultaneous equations with two unknowns

Apply algebraic procedures in solving problems